2017
DOI: 10.1080/09540121.2017.1281877
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric symptom burden in older people living with HIV with and without cognitive impairment: the UCSF HIV over 60 cohort study

Abstract: Psychiatric comorbidities are common in people living with HIV (PLWH) and adversely affect life satisfaction, treatment adherence and disease progression. There are few data to inform the burden of psychiatric symptoms in older PLWH, a rapidly growing demographic in the U.S. We performed a cross-sectional analysis to understand the degree to which symptom burden was associated with cognitive disorders in PLWH over age 60. Participants completed a standardized neuropsychological battery and were assigned cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…While depressive symptoms and cognitive impairment are common co-morbidities in HIV-infection (1, 28, 29, 45, 46), several studies suggest psychiatric and neurocognitive sequelae of HIV-infection are largely independent of each other (6972). A recent report of depression in older people living with HIV on ART showed that despite greater overall depressive symptom burden among HIV-infected participants compared to HIV-uninfected controls, depressive symptoms were not associated with HIV-associated neurocognitive disorders, suggesting a disconnect between depressive and neurocognitive symptoms in HIV infection (72). Thus, findings in the present study along with studies from the literature highlight that in the context of HIV infection, etiological mechanisms underlying depressive symptoms may be distinct from mechanisms that influence cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…While depressive symptoms and cognitive impairment are common co-morbidities in HIV-infection (1, 28, 29, 45, 46), several studies suggest psychiatric and neurocognitive sequelae of HIV-infection are largely independent of each other (6972). A recent report of depression in older people living with HIV on ART showed that despite greater overall depressive symptom burden among HIV-infected participants compared to HIV-uninfected controls, depressive symptoms were not associated with HIV-associated neurocognitive disorders, suggesting a disconnect between depressive and neurocognitive symptoms in HIV infection (72). Thus, findings in the present study along with studies from the literature highlight that in the context of HIV infection, etiological mechanisms underlying depressive symptoms may be distinct from mechanisms that influence cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Through proxy reporting, HIV-infected elders over age 60 more frequently experienced agitation, depression, anxiety, apathy, irritability and sleep difficulties compared to health controls, regardless of cognitive status. [61] Similarly, neuropsychiatric symptoms such as apathy, agitation and anxiety affect more that 80% of AD patients during the course of the disease and may be present at the earliest AD stages, while their severity worsens throughout the disease progression. [62-65] Data from HIV-infected patients with reliable and proximal informants would add greatly to understanding how the symptom and neuropsychiatric presentations of mild disease differs from early AD.…”
Section: Insight From the Clinical Presentationmentioning
confidence: 99%
“…Not only are older persons more vulnerable to more persistent depressive symptoms despite treatment [92], but depression in this older population is associated with cognitive impairments in and of itself: in the domains of executive functioning, processing speed, episodic memory, all of which are already impaired by the process of cognitive aging [93, 94]. In HIV-positive adults, this higher incidence of cognitive and mood disorders [95] can also exacerbate risk of substance abuse, relative to younger HIV-positive adults or older HIV-negative adults [96] and the combination of these factors may impact quality of life [97, 98]. Treating mood symptoms without addressing cognitive impairments may be one reason that depression symptoms are less responsive to treatment in older and HIV-positive persons, and more consistent monitoring and treatment of both may lead to better outcomes.…”
Section: Normal Cognitive Agingmentioning
confidence: 99%